Transformation of Madrasah Education Management: The Implementation of Performance-Based Planning and Budgeting Policies - Perdana, Taslim; Ritonga, Mahyudin (EDUPEDIA Publisher, 2026)
Purpose – This study aims to examine the role of Madrasah Self-Evaluation (EDM) and the electronic Madrasah Work and Budget Plan (e-RKAM) in transforming madrasah education management through the implementation of performance-based planning and budgeting policies. The study is grounded in the growing demand for data-driven, transparent, and accountable governance to improve the quality of madrasah education. Methodology – This research employed a descriptive-analytical qualitative approach. Data were collected through document analysis of policy regulations, technical guidelines, and implementation reports related to EDM and e-RKAM, as well as a review of relevant literature on education management and performance-based budgeting. The analysis focused on examining the integration process, implementation mechanisms, and managerial implications of EDM and e-RKAM within madrasah governance. Findings – The integration of EDM and e-RKAM establishes a structured management cycle that links quality evaluation, planning, budgeting, implementation, monitoring, and accountability. EDM provides objective data on madrasah performance through measurable indicators, while e-RKAM ensures that budgeting decisions align with identified priority needs. This integration contributes to greater transparency, accountability, and more effective resource utilization. However, challenges remain, particularly in terms of human resource capacity, digital literacy, and infrastructure readiness. Novelty – This study offers a conceptual contribution by presenting EDM and e-RKAM as an integrated performance-based management framework rather than as separate administrative instruments. It highlights how the alignment between self-evaluation data and electronic budgeting systems can drive a paradigm shift in madrasah governance. Significance – The results of this study are beneficial for madrasah leaders, policymakers, education administrators, and stakeholders within the Ministry of Religious Affairs as a reference for strengthening data-driven decision-making and improving the quality and accountability of madrasah education management